Recent Advances of Upscaling Methods for the Simulation of Flow Transport Through Heterogeneous Porous Media (Journal of Computational Mathematics, 2006)
We review some of our recent efforts in developing upscaling methods for simulating the flow transport through heterogeneous porous media. In particular, the steady flow transport through highly heterogeneous porous media driven by extraction wells and the flow transport through unsaturated porous media will be considered.